TEACHING SPEAKING WITH GOSSIPING IN THE PERIOD OF PANDEMIC - Utami Ratna Swari (Universitas Aki, 2020)
The mastery of speaking is important in English language learning, even in the period of pandemic, due to the outbreak of COVID 19. Teacher should use interesting method to keep students engage in the teaching and learning process. One of methods in teaching speaking is by using gossiping. The aims of this research is to describe the application of gossiping as one of the techniques in the teaching speaking which focuses on intermediate level students. This research will explain: 1) gossiping and its advantages, 2) topics to be gossiped in speaking English activity, 3) the application of gossiping in teaching speaking. Gossiping as a talk with inspiration and emotion has three major function: a) As a mechanism of information exchange, b) As an entertainment, c) As a portal to brings groups together and d) As a way to be influential. Topics to be gossiped in speaking can be someone famous or popular. The conclusion shows that there is an example of teaching procedure in speaking English using gossiping and it can be a way to keep students engage in the process of teaching speaking, thus it an improve the students mastery in speaking skill.